Space arrangement of service areas and furnishings of selected public libraries in Metro Manila - Elizes, Zyril D.; Dizon, Leticia B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
This study is an investigation of the space arrangement of service areas and furnishings of the seven selected public libraries in Metro Manila (Caloocan City Library, Makati City Library, Malabon Public Library, Mandaluyong City Library, Marikina City Library, Pasig City Library and Museum, and Quezon City Library). the specific objectives of the study are: 1) to identify the furnishings that are presently used in the selected public libraries; 2) to ascertain the functional service areas in the selected public libraries; 3) to determine the total space assigned for each service areas; 4) to know if these libraries follow standards for space arrangement of service areas and furnishings; and 5) know the perception of the users regarding the matter.
The major findings are: 1)The Makati City Library and Pasig City Library and Museum almost met the minimum standard of furnishings based on the standards given by the Committee on Standards for Public Libraries. 2) Majority of the libraries use artificial lighting (fluorescent) and ventilation (electric fan and air conditioner). 3) All the studied libraries' service areas are supervised by a librarian. 4) Majority of the libraries are in rectangular-shaped plan which is the typical shape found in other types of the library. 5) No proposed standard regarding space arrangement of service areas and furnishings has been followed in all libraries. The librarians are the ones who set the general reading interior arrangement of their libraries. 6) The common library sections in the libraries are: Chief Librarian's Office, Children's Department, Circulation Area, Staff Office, Special Collections Area, Periodical area, Filipiniana Area, General Reading Area and Washroom. 7) The Special Collection Area makes each library unique. 8) The largest floor area common to most of the libraries in the General Reading Areas. 9) Most libraries got a score of 8, where 10 is the highest and 1 is the lowest regarding the library's space arrangement of service areas and furnishings. 10) Most of the librarians do not know that there is the Minimum standards for Public Libraries in the Philippines prepared by the Committee on Standards for Public Libraries.
The study recommends the following: 1) The librarians, at least the Chief Librarian, should be aware of the existence of the Minimum Standards for Public libraries in the Philippines. 2) The librarians can make their own proposed standards regarding space arrangement of service areas and furnishings if they do not follow any standard; 3) Every time the librarians arrange their sections, it is better if they ask the perceptions of the users about the new arrangement of the library so that they can make the best possible arrangement where everyone can find comfort and satisfaction in using their library. 4) The government should provide adequate budget for the public library. 5) air-conditioning in libraries should be installed to make libraries more conducive for reading and studying especially in our tropical country 6) The equipment that produces noise should be placed far from the General reading Area to avoid disturbances. 7) The Children's Department should be kept distant from the General Reading Area.
Computer print out.
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Public libraries -- Philippines -- Manila Metropolitan Area; Public libraries -- Space utilization -- Philippines -- Manila Metropolitan Area